Strengthening Legal Frameworks and Patient Safety: A Narrative Review of Medical and Dental Malpractice in Indonesia - Mustafa, Ghulam; Darmawan, Ede Surya (UI Scholars Hub, 2025)
Many cases of medical and dental malpractice in Indonesia are still related to patient safety and healthcare quality. This narrative review aims to identify solutions that can be implemented. The main focus is to compare the incidence of malpractice in clinical medical and dental practice, emphasizing legal implications, coverage, and internal organizational issues. A systematic literature search was conducted through databases such as Pubmed, ScienceDirect, Google Scholar, Springer, Garuda, and other online databases. Articles published no later than 2024. Eleven studies were selected that discussed the problem of malpractice in Indonesia. Independent screening and critical appraisal were carried out to minimize bias, and data were retrieved and assessed through narrative synthesis. The results showed limited or lack of informed consent, non-compliance, administrative negligence, poor communication, and laws on medical malpractice. Causal factors, such as negligence in the operating room, misdiagnosis, and lack of consent forms, were common and most often resulted in patient injury or death. This review also explains a lack of studies related to this due to the poorly organized data collection system on complaints of medical malpractice in the country and the lack of adequate legal governance regarding dental malpractice. Regulations related to legal practices in Indonesia are still poorly organized, and even in similar cases, consistent enforcement is not guaranteed. These factors indicate the need for an evaluation of the healthcare system in Indonesia. Suggestions that can be given are to involve the community in the informed consent process, improve medical training, and improve the legal system so that these incidents can be reduced in number and patients feel protected.